2006
DOI: 10.1038/sj.jid.5700237
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Desmoglein 4 Gene Underlie Localized Autosomal Recessive Hypotrichosis with Monilethrix Hairs and Congenital Scalp Erosions

Abstract: Localized autosomal recessive hypotrichosis (LAH) is a recently defined disorder characterized by fragile, short, sparse hairs on the scalp, trunk, and extremities. Mutations in desmoglein 4 (DSG4), a novel member of the desmosomal cadherin family that is expressed in the hair follicle as well as the suprabasal epidermis, have been found to underlie LAH. Thus far, the allelic series includes a recurrent intragenic deletion identified in affected Pakastani kindreds and a missense mutation detected in an Iraqi f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 31 publications
5
70
0
Order By: Relevance
“…Interestingly, the clinical features of patients harboring this mutation are a focal nonstriated form of PPK associated with discrete keratinization at sites exposed to mechanical trauma, such as the knees, ankles, and finger knuckles, and with mild nail dystrophy. In addition, Keren et al 109 reported a family affected with a diffuse nonstriated form of PPK that harbored a recurrent mutation in Dsg1, previously associated with cases of SPPK. These studies reveal that mutations in Dsg1 are not exclusively associated with SPPK.…”
Section: Desmogleinmentioning
confidence: 99%
“…Interestingly, the clinical features of patients harboring this mutation are a focal nonstriated form of PPK associated with discrete keratinization at sites exposed to mechanical trauma, such as the knees, ankles, and finger knuckles, and with mild nail dystrophy. In addition, Keren et al 109 reported a family affected with a diffuse nonstriated form of PPK that harbored a recurrent mutation in Dsg1, previously associated with cases of SPPK. These studies reveal that mutations in Dsg1 are not exclusively associated with SPPK.…”
Section: Desmogleinmentioning
confidence: 99%
“…This amino acid substitution is located within a highly conserved motif (RAL) corresponding to the HAV region of classical cadherins, a domain that is important in cell-cell adhesion. In 2006, further missense, splice site, frameshift and nonsense mutations in the DSG4 gene were reported [85][86][87]. However, the phenotype in these cases was described as autosomal recessive monilethrix.…”
Section: Desmoglein 4 Mutations Cause Hair Abnormalitiesmentioning
confidence: 99%
“…More recently, DSG4 gene mutations were found to be associated with human monilethrix hairs (Shimomura et al, 2006;Amagai, 2010). These studies convincingly demonstrate that DSG4 plays an important role in regulating the proliferation and differentiation of hair follicles in mammals (Schaffer et al, 2006;El-Amraoui and Petit, 2010). Although our knowledge about the sheep DSG4 gene remains limited, some DNA sequences of sheep that are homologous to this gene in other organisms are available in the GenBank.…”
Section: Introductionmentioning
confidence: 97%